The Impact of a Proposed Strategy for Teaching Number Theory according to the Theoretical Proof Model Applied on the Achievement of Students of the College of Basic Education - Saaduldeen, Luma Akram; Mostafa, Enas Yonues; Mohammad Tawfiq, Saja Othman (Journal of Tikrit University for Humanities, 2023)
The research aimed to identify the impact of a proposed strategy based on the model of theoretical proof on the achievement of first-grade students in the subject theory of numbers, and a zero hypothesis was formulated. The control and the experimental and control groups were taught by the researcher. Teaching continued in the second semester with (18) lessons. The researchers prepared an achievement test in the theory of numbers consisting of six questions distributed evenly according to Merrill levels (remembering and application and exploration) and the total score for it (30). Its apparent validity, content, and consistency consistency were verified using the alpha Cronbach equation. The results were analyzed using the t-test for two independent samples. The research found that there is no statistically significant difference between the average achievement of the students of the experimental and control groups. With a set of recommendations, a number of studies were proposed to complement the current research.